Analysis of the Effect of Gross Regional Domestic Product and Human Development Index on Poverty in North Sumatra 2013 – 2022 - Lastiara Agmonaria Veronica Manik; Nova Novita Pardede; Jeremi Putranta Tampubolon (Indonesian Journal of Advanced Research, 2023)
This study The aim of this study was to determine the effect of the Gross Regional Domestic Product and the Human Development Index on Poverty in North Sumatra in 2013-2022. The data used in this study is quantitative data sourced from secondary data obtained from the official website of the Central Government. Central Bureau of Statistics of North Sumatra. The method used in this study is multiple linear regression analysis with the help of e-views 10 software. The results show that GRDP has a negative and insignificant effect on Poverty in North Sumatra in 2013 - 2022, while HDI has a positive and insignificant effect on Poverty in Sumatra North in 2013 - 2022.